Personality, plasticity and predation: linking endocrine and behavioural reaction norms in stickleback fish. (13th January 2015) - Fürtbauer, Ines; Pond, Alice; Heistermann, Michael; King, Andrew J.
Summary: Predation plays a fundamental role in evolutionary processes, driving changes in prey morphology, physiology and behaviour. With organisms being increasingly exposed to rapid environmental changes, there is growing interest in understanding individual phenotypic plasticity in response to changes in predation pressure. Behavioural and physiological responses to predator exposure are of particular interest as differences in predation pressure are often reflected in correlated suites of behavioural and hormonal profiles across populations. Within populations, the association between endocrine profiles and behaviour is less understood and often lacking. Adopting a reaction norm approach and a repeated measures design, we assessed within‐population effects of changes in perceived predation risk on endocrinology and behaviour in three‐spined sticklebacks ( Gasterosteus aculeatus ). We repeatedly exposed subjects to a robotic model predator and assessed their behavioural response. The fish showed consistent behavioural profiles and were less active and shyer when predation risk was higher. Using non‐invasive waterborne hormone analysis, we assessed basal cortisol as well as the cortisol response to changes in predation risk. Individuals showed significantly higher cortisol levels following exposure to the model predator. Individual post‐predator exposure cortisol was repeatable but unrelated to behavioural responses. Accounting for between versus within‐subject effects, we found that basal cortisol and shyness were positively related within individuals, that is individuals overall were shyer on days they had higher cortisol levels. We also tested if basal testosterone predicted risky behaviour and found no evidence for this hypothesis. No individual differences in hormonal or behavioural responses to changes in predation risk were found, suggesting that individuals are not constrained by their personalities in their ability to cope with a potentially harmful threat. Overall, we show that individuals of different personalities are equally 'flexible' in their response to changes in predation pressure. Our study offers novel insight into consistent individual differences and plasticity in hormones and behaviour as well as their interplay within populations. Future studies should assess the applicability of these findings to other changes in the environment, as well as the effects of social context on endocrine and behavioural reaction norms. Abstract : Lay Summary